Pneumothorax in critically COVID-19 patients with mechanical ventilation (Medical Journal of Indonesia, 2021)
Coronavirus disease 2019 (COVID-19) is a public health emergency caused by SARS-CoV-2. A few studies reported pneumothorax in patients with COVID-19. Pneumothorax is associated with an increased morbidity and mortality. Hence, it should be considered during the treatment and follow-up of patients with COVID-19. Herein, we reported four cases of pneumothorax in critical COVID-19 patients hospitalized in the ICU and treated with a mechanical ventilation. All patients were diagnosed with COVID-19, type 1 respiratory failure, and acute respiratory distress syndrome. All patients developed pneumothorax during mechanical ventilation, although the ventilator settings were set to lung-protective strategy.